1970
DOI: 10.1159/000130093
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy and mechanisms of karyotypic diversification in Amphibia

Abstract: Polyploid species were described in amphibians of the family Ceratophrydidae (Procoela). Tetraploid (4N = 44) and octoploid (8N = 104) karyotypes resulted apparently by duplication of ancestral genomes with N = 11 and N = 13 respectively. The meiosis of the polyploid species was regular, producing euploid gametes. Comparative cytophotometric measurements confirmed a DNA increase in a 1:2:4 ratio, as expected from cytological observations. Fourteen species and one subspecies of the families Ceratophrydidae, Lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0
5

Year Published

1970
1970
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 3 publications
7
21
0
5
Order By: Relevance
“…The C-banding is centromeric in both L. fuscus and L. latrans, although the constitutive heterochromatin was centro/pericentromeric in all the specimens of both species, as well as additional C-positive regions in some chromosomes, such as the telomeric or interstitial regions, or even the Ag-NOR sites. ( Beçak et al 1970, Silva et al 2000Amaro-Ghilardi et al 2004), as observed in the present study. There are some divergent species, however, such as Leptodactylus silvanimbus and Leptodactylus marmoratus (= Adenomera No between-population differences were found in the C-banding of L. fuscus.…”
Section: Discussionsupporting
confidence: 82%
“…The C-banding is centromeric in both L. fuscus and L. latrans, although the constitutive heterochromatin was centro/pericentromeric in all the specimens of both species, as well as additional C-positive regions in some chromosomes, such as the telomeric or interstitial regions, or even the Ag-NOR sites. ( Beçak et al 1970, Silva et al 2000Amaro-Ghilardi et al 2004), as observed in the present study. There are some divergent species, however, such as Leptodactylus silvanimbus and Leptodactylus marmoratus (= Adenomera No between-population differences were found in the C-banding of L. fuscus.…”
Section: Discussionsupporting
confidence: 82%
“…Interspecific variability of DNA content has also been reported in Amphibia, including Odontophrynus species (Beçak et al, 1970a). Minas Gerais, Goiás (Brazil) Beçak et al, 1966Beçak et al, , 1967aBeçak et al, ,b, 1970a O. occidentalis, 2n Barrio and Pistol, 1972;Ruiz et al, 1982 ---11,11 Cordoba (Argentina) Bogart and Wasserman, 1972 O. americanus, 4n ---11,11,11,11 São Paulo, Minas Gerais, Paraná (Brazil), Argentina Beçak et al, 1966;Beçak and Beçak, 1974b;Saez and Brum-Zorrilla, 1966;Schmidt et al, 1985 -8 10 11,11,11,11 São Paulo (Brazil) Beçak and Beçak, 1974b 4,4,4,4 --11,11,11,11 Rio Grande do Sul (Brazil), Santa Lúcia (Uruguay) Beçak and Beçak, 1974b ---11,11,11,11 TreintayTres and Maldonado (Uruguay) and Tucuman and Azul (Argentina) Barrio and Pistol de Rubel, 1972 4,4,4,4 --11,11,11,11 Uruguay and Argentina Barrio and Pistol de Rubel, 1972 .…”
Section: Intra-and Interspecific Chromosomal Polymorphisms In Odontopmentioning
confidence: 89%
“…Odontophrynus americanus* 4n = 44 N = 11 Beçak, 1967a;Beçak et al, 1966Beçak et al, , 1967bBogart, 1967;Barrio and Pistol de Rubel, 1972 Odontophrynus cordobae 4n = 44 N = 11 Martino and Sinsch, 2002 Ceratophrys dorsata (= C. aurita)* 8n = 104 N = 13 Beçak, 1967a;Beçak et al, 1967b Ceratophrys ornata* 8n = 104 N = 13 Bogart, 1967;Barrio and de Chieri, 1970a,b;Bogart and Wasserman, 1972 Eleutherodactylus binotatus (post-polyploidy)*** 2n = 22 N = 11 Beçak and Beçak, 1974a Pleurodema bibroni (= P. darwinii) 4n = 44 N = 11 Barrio and de Chieri, 1970a,b Pleurodema kriegi** 4n = 44 N = 11 Barrio and de Chieri, 1970a,b Myobatrachinae Neobatrachus sudelli** 4n = 48 N = 12 Morescalchi, 1970 Neobatrachus sutor** 4n = 48 N = 12 Morescalchi, 1970 Hylidae Hyla versicolor 4n = 48 N = 12 Wasserman, 1970;Bogart and Wasserman, 1972 Phyllomedusa burmeisteri (P. tetraploidea)* 4n = 52 N = 13 Beçak et al, 1970a Pipidae Xenopus vestitus** 4n = 72 N = 18 Tymowska and Fischberg, 1973;Tymowska et al, 1977;Tymowska, 1991 Xenopus ruwenzoriensis** 6n = 108 N = 18 …”
Section: References Leptodactylidaementioning
confidence: 99%
See 1 more Smart Citation
“…Así el tipo 3 de evolución postulado por RENDEL (1965) que involucra el incremento de material genético (por poliploidía, entre otros mecanismos) posibilitaría la aparición de novedades evolutivas manteniendo, mientras, las más viejas. La poliploidía proveería además de un mayor número de posibles combinaciones genéticas como consecuencia de la segregación independiente de homólogos multivalentes (BEÇAK et al,1970). Es decir que la "nueva" adquisición del estado poliploide sería recién el comienzo de una etapa evolutiva en este taxón.…”
Section: Discussionunclassified